Inhibitory effects of water caltrop pericarps on the growth of human gastric cancer cells in vitro - Lin, Qiusheng; Shen, Junhui; Ning, Ying; Shen, Shengrong; Das, Undurti N (Current pharmaceutical design, 2013)
Water caltrop is a popular traditional vegetable in China, and its pericarps are always wasted. In the present work reported here, pericarps from three different Chinese water caltrop cultivars were collected and extracted using 70% methanol and hot water. All the extracts contained significant amounts of polyphenols (183.7-201.7 mg GAE/g), flavonoids (34.3-54.6 mg RE/g) and saponins (23.2- 36.3 mg GRE/g). These extracts exhibited strong antioxidant capacity as assessed by DPPH, ABTS and FRAP methods. High correlations were found in DPPH, ABTS and polyphenols, FRAP and saponins. All the three extracts inhibited proliferation of SGC7901 human gastric cancer cells and HepG2 human hepatocarcinoma cells in a dose dependent manner without detectable cytotoxicity on HUVEC normal cells. Flow cytometry showed that apoptosis of SGC7901 and HepG2 cells was induced by water caltrop extracts while HUVEC cells were relatively resistant to apoptosis. Hot water extracts showed similar bioactivities as methanol extracts, which indicated that hot water could be used to extract bioactive compounds instead of organic solvents. These results suggest that water caltrop pericarps could be explored for their potential as anti-cancer drugs in future studies.